Impact of COVID-19 pandemic restrictions on ST-elevation myocardial infarction: a cardiac magnetic resonance imaging study. (11th October 2021) - Lechner, Ivan; Reindl, Martin; Tiller, Christina; Holzknecht, Magdalena; Troger, Felix; Fink, Priscilla; Mayr, Agnes; Klug, Gert; Bauer, Axel; Metzler, Bernhard; Reinstadler, Sebastian J
Abstract: Aims: The severity of myocardial tissue damage following ST-elevation myocardial infarction (STEMI) strongly determines short- and long-term prognosis. This study explored the impact of the coronavirus disease 2019 (COVID-19) pandemic and associated public health restrictions on infarct severity. Methods and results: STEMI patients treated with primary percutaneous coronary intervention (PCI) and included in the prospective Magnetic Resonance Imaging in Acute ST-Elevation Myocardial Infarction (MARINA-STEMI) cohort study from 2015- 2020 ( n = 474) were categorized according to (i) timeframes with and without major public health restrictions in 2020, and (ii) timeframes of major public health restrictions during 2020 and during the corresponding timeframes between 2015-2019. Myocardial damage was evaluated by cardiac magnetic resonance imaging. During major public health restrictions in 2020 ( n = 48), there was an increase in infarct size (22 [IQR 12-29] vs. 14 [IQR 6-23]%, P < 0.01), a higher frequency (77% vs. 52%, P < 0.01) and larger extent of microvascular obstruction (1.5 [IQR 0.1-11.4] vs. 0.2 [IQR 0.0-2.6]%, P < 0.01) and a higher rate of intramyocardial haemorrhage (56% vs. 34%, P = 0.02) as compared to the phases without major restrictions in 2020 ( n = 101). These findings were confirmed in adjusted analysis and were consistent when comparing patients admitted in 2020 versus patients admitted in the "pre-pandemic" era (2015-2019). Patient characteristics were comparable between groups, except for a significantly longer total ischemia time ( P < 0.01) and higher frequency of pre-PCI Thrombolysis in Myocardial Infarction (TIMI) flow 0 during times of major restrictions ( P = 0.03). Conclusion: This study provides novel mechanistic insights demonstrating a significant increase in myocardial damage in STEMI patients admitted during the COVID-19 pandemic with a temporal relation to major public health restrictions. Graphical Abstract: